Cardiac Rehabilitation — Challenges, Advances, and the Road Ahead - Thomas, Randal J. (The New England journal of medicine, 2024)
Cardiac rehabilitation provides evidence-based, secondary prevention after a cardiovascular event. This review addresses the benefits of cardiac rehabilitation programs and current barriers to participation.